Sequences, Subsequences, and Consequences International Workshop, SSC 2007, Los Angeles, CA, USA, May 31 - June 2, 2007, Revised Invited Papers - Golomb, Solomon W.; Gong, Guang; Helleseth, Tor.; Song, Hong-Yeop.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
These are the proceedings of the Workshop on Sequences, Subsequences, and Consequences that was held at the University of Southern California (USC), May 31 - June 2, 2007. There were three one-hour Keynote lectures, 16 invited talks of up to 45 minutes each, and 1 “contributed” paper. The theory of sequences from discrete symbol alphabets has found practical applications in many areas of coded communications and in cryptography, - cluding: signal patterns for use in radar and sonar; spectral spreading sequences for CDMA wireless telephony; key streams for direct sequence stream-cipher cryptography; and a variety of forward-error-correctingcodes. The workshopwasdesigned to bring leading researcherson “sequences”from aroundtheworldtopresenttheirlatestresults,interchangeinformationwithone another, and especially to inform the larger audience of interested participants, includingfaculty,researchers,scholars,andstudentsfromnumerousinstitutions, as well as the readers of these proceedings, about recent developments in this important ?eld. There were invited speakers from Canada, China, Germany, India, Israel, Norway, Puerto Rico, and South Korea, in addition to those from the USA. Support for the workshop was generously provided by the O?ce of the Dean of the Viterbi School of Engineering, by the Center for Communications Research (CCR-La Jolla), and by the United States National Science Foundation (NSF). This support is hereby gratefully acknowledged.
Periodic Binary Sequences: Solved and Unsolved Problems -- On Boolean Functions Which Are Bent and Negabent -- Strongly Primitive Elements -- The Perfect Binary Sequence of Period 4 for Low Periodic and Aperiodic Autocorrelations -- On the Dual of Monomial Quadratic p-ary Bent Functions -- A New Family of Gold-Like Sequences -- Sequencings and Directed Graphs with Applications to Cryptography -- Double Periodic Arrays with Optimal Correlation for Applications in Watermarking -- Sequences for Phase-Encoded Optical CDMA -- Packing Centrosymmetric Patterns of n Nonattacking Queens on an n×n Board -- Cyclotomic Mapping Permutation Polynomials over Finite Fields -- Single-Track Gray Codes and Sequences -- The Asymptotic Behavior of ?-Adic Complexity with ?2?=???2 -- Shannon Capacity Limits of Wireless Networks -- Some Mysterious Sequences Associated with LDPC Codes -- Remarks on a Sequence of Minimal Niven Numbers -- The Linear Vector Space Spanned by the Nonlinear Filter Generator -- Existence of Modular Sonar Sequences of Twin-Prime Product Length -- Randomness and Representation of Span n Sequences -- On Attacks on Filtering Generators Using Linear Subspace Structures.
Keywords: Computers; Coding theory; Information theory; Data encryption (Computer science).; Computer science—Mathematics.; Computer communication systems; Theory of Computation; Coding and Information Theory; Cryptology; Discrete Mathematics in Computer Science; Computer Communication Networks